PENGARUH CURRENT ASSET SAVING ACCOUNT (CASA) DAN FEE- BASED INCOME (FBI)TERHADAP RETURN ON ASSET (ROA) PADA BANK JABAR-BANTEN SYARIAH (BJBS) PERIODE 2016-2020 - Ade Monika; Arif Luqman Hakim; Ali Nur Ahmad (DPPM Universitas Pelita Bangsa, 2022)
This study examines the effect of Current Account Saving Account (CASA) and Fee-Based Income (FBI) on Return On Assets (ROA) at Bank BJB Syariah for the 2016-2020 period. This study aims to determine whether or not there is an effect of Current Account Saving Account (CASA) and Fee Based Income (FBI) on Return On Assets (ROA) either partially or simultaneously at Bank BJB Syariah for the 2016-2020 period. In this study the authors used descriptive quantitative methods, using secondary data. The subjects in this study were the monthly reports of Bank BJB Syariah during the 2016-2020 period with a sample size of 60. The analytical techniques used were Descriptive Statistics Test, Classical Assumption Test, Simple Regression Test and Multiple Regression Test using the help of the IBM SPSS Stratistic 24 application. The results of the study This shows that partially the Current Account Saving Account (CASA) variable has no effect on Return On Assets (ROA), then the Fee-Based Income (FBI) variable has a negative and significant effect on Return On Assets (ROA). And simultaneously Current Account Saving Account (CASA) and Fee-Based Income (FBI) variables have a positive and significant effect on Return On Assets (ROA).